Role of Department for geography in Maribor at development of Slovene didactics of geography from the second half of 20th Century till today - Kolnik, Karmen (Journal for Geography, 2013)
A short overview of fifty-year development of teaching geography in Maribor is introduced in three time periods: from the point of view of development of study programs, from initial two-year higher education study to today’s five-year university, from the view of didactics of geography as one of the basic study programs of future geography teachers and from the view point of teaching and scientific part of holders and implementers of didactics of geography.